THE PROJECT-BASED CURRICULUM AND COMPLEXITY IN SCHOOL: POSSIBILITIES FOR AN EDUCATION ON VALUES - Ricardo Fernandes Pátaro (Editora da Universidade de Santa Cruz do Sul, 2013)
This paper is derived from a dissertation and the main goal is to argue how the project-based curriculum, in a perspective of complexity, can offers some possibilities for an education on values introducing studies of nowadays social problems into the school. To achieve the objectives was considered a project developed with a ten years old students. The investigation was based on project activities and daily field. As a result we have demonstrated the project-based curriculum - using the complexity, interdisciplinary and transversality as references - can help school to combine the disciplinary knowledge to the ethical formation. The investigation has show that the project-based curriculum may lead schools to succeed in implementing an education in values, pointing out some directions to develop citizens who can deal with diversity and conflicts as well as capable of get indignant with the injustices and have disposal to individual and collective welfare.